Investigation of Triazavirin Antiviral Activity Against Tick-Borne Encephalitis Pathogen in Cell Culture - S. YA. Loginova; S. V. Borisevich; V. L. Rusinov; U. N. Ulomsky; V. N. Charushin; O. N. Chupakhin (Антибиотики и Химиотерапия, 2020)
The efficacy of Triazavirin against the tick-borne encephalitis virus was estimated in the sensitive cell culture vs. the active drug Ribavirin®. In a concentration of 128 mcg/ml Triazavirin was shown active in inhibition of the tick-borne encephalitis virus reproduction (strain Sofiin) by accumulation in the SKEV cell culture.